2017
DOI: 10.1038/s41598-017-09403-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Bidirectional Activity of Bacillus nanoRNase NrnA

Abstract: NanoRNAs are RNA fragments 2 to 5 nucleotides in length that are generated as byproducts of RNA degradation and abortive transcription initiation. Cells have specialized enzymes to degrade nanoRNAs, such as the DHH phosphoesterase family member NanoRNase A (NrnA). This enzyme was originally identified as a 3′ → 5′ exonuclease, but we show here that NrnA is bidirectional, degrading 2–5 nucleotide long RNA oligomers from the 3′ end, and longer RNA substrates from the 5′ end. The crystal structure of Bacillus sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 47 publications
2
24
2
Order By: Relevance
“…Although the amino acid similarity among DHH superfamily members is less than 20%, a Dali search revealed that their three-dimensional structures are notably similar. The topology of PfuHAN_DND is similar to the structures of several DHH superfamily members (Figure 4D , and Supplementary Figure S9 ), including bacterial RecJs ( 44–46 ), GAN ( 47 ), NrnA ( 48 ), and PPase ( 49 ). Each of them has an N-terminal DHH and a C-terminal DHHA1/2 domain, suggesting they might have evolved from a common ancestor.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…Although the amino acid similarity among DHH superfamily members is less than 20%, a Dali search revealed that their three-dimensional structures are notably similar. The topology of PfuHAN_DND is similar to the structures of several DHH superfamily members (Figure 4D , and Supplementary Figure S9 ), including bacterial RecJs ( 44–46 ), GAN ( 47 ), NrnA ( 48 ), and PPase ( 49 ). Each of them has an N-terminal DHH and a C-terminal DHHA1/2 domain, suggesting they might have evolved from a common ancestor.…”
Section: Resultsmentioning
confidence: 63%
“…Unlike BsuNrnA, which forms a dimer via interactions between two DHHA1 domains ( 48 ), PfuHAN forms a symmetric trimer through both DHH and DHHA1 domains, as well as the helix linker α13 (Figure 7A and B ). The interaction strength of each subunit is primarily dictated by hydrogen bonds and salt bridges.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations